2020
DOI: 10.1038/s41467-020-14716-z
|View full text |Cite
|
Sign up to set email alerts
|

Disordered protein-graphene oxide co-assembly and supramolecular biofabrication of functional fluidic devices

Abstract: Supramolecular chemistry offers an exciting opportunity to assemble materials with molecular precision. However, there remains an unmet need to turn molecular self-assembly into functional materials and devices. Harnessing the inherent properties of both disordered proteins and graphene oxide (GO), we report a disordered protein-GO co-assembling system that through a diffusion-reaction process and disorder-to-order transitions generates hierarchically organized materials that exhibit high stability and access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 52 publications
1
56
0
Order By: Relevance
“…La et al (2013) showed that GO had promising applications in bone regeneration. In another recent study (Wu et al, 2020), an innovative coassembled ELK1‐GO system was used to exploit the functionalities of both the proteins and GO. This coassembled ELK1‐GO system enabled the multiscale organization which offered the biological materials with well‐defined tubular microstructures for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…La et al (2013) showed that GO had promising applications in bone regeneration. In another recent study (Wu et al, 2020), an innovative coassembled ELK1‐GO system was used to exploit the functionalities of both the proteins and GO. This coassembled ELK1‐GO system enabled the multiscale organization which offered the biological materials with well‐defined tubular microstructures for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SF, other proteins such as elastin‐like polypeptides, [ 34,45 ] plant protein fibrils, [ 46 ] soy protein, [ 47 ] gelatin [ 48 ] have been demonstrated as effective coassembly agents. Zhou et al.…”
Section: Proteins As Structure‐control Agentsmentioning
confidence: 99%
“…A new material composed of graphene oxide (GO) and protein can be used with 3-D printing to generate tissue-like vascular structures. The study, which was published in Nature Communications , 1 involved an international team that included scientists from the University of Nottingham in the UK.…”
Section: New Biomaterials Can Be 3-d Printedmentioning
confidence: 99%
“…The development of novel biomaterials could have countless applications and benefit many fields. Proteins are being investigated as elements of multicomponent systems, and elastin-like recombinamers (also known as recombinantly produced elastin-like polypeptides) such as the one employed in the study by Wu et al 1 have already been used to create biocompatible materials. The inclusion of graphene as a building block in the design of such biomaterials would confer them improved complexity and functionalities, given the 2-D structure and thermal and mechanical properties of graphene.…”
Section: New Biomaterials Can Be 3-d Printedmentioning
confidence: 99%